Preferences for Preoperative Education: A Qualitative Study of the Patient Perspective. Issue 10 (11th October 2021) - Rockefeller, Nicholas F.; Jeppson, Peter; Komesu, Yuko M.; Meriwether, Kate V.; Ninivaggio, Cara; Dunivan, Gena
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aim of this study is to identify and describe the information that is important to patients in preparation for surgery for pelvic floor disorders. Methods: This qualitative study enrolled English- and Spanish-speaking patients who had undergone surgery for pelvic floor disorders in semistructured focus groups. We explored patients' attitudes and views regarding preoperative education, postoperative experiences, and quality of pain management. Focus groups were conducted until thematic saturation was reached. Deidentified focus group transcripts were analyzed with line-by-line coding and organized into themes using a team-based process. Results: Four focus groups were conducted, 2 with English-speaking women (n = 14) and 2 with Spanish-speaking women (n = 10). Participants identified as non-Hispanic White 13/24 (54%) or Hispanic 11/24 (46%); 83% had at least a high school education and 50% had a bachelor's degree. Women reported 5 thematic domains of information that they deemed important for patients to know preoperatively: (1) preparation for surgery; (2) postoperative pain control expectations; (3) postoperative activity restrictions; (4) communication with care team; and (5) care experiences. Conclusions: This study identifies information that is important to patients undergoing pelvic floor surgery. These patient-centered themes go beyond routine preoperative education and counseling. This information will aid future studies regarding the incorporation of patient-centered preoperative education and expectation setting with respect to improved pain control, patient satisfaction, and overall surgical experience.